The multiple application of the "Portable Swim specific Test and Training device (PSTT)" - Kunze, K.; Schega, L. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The "Portable Swim specific Test and Training device (PSTT)" (Schega et al., 2000) offers a multitude of possibilities for application due to ist different options of operation. It can be used for application oriented research to estimate the passive drag in water or cW-values. In swimming training the PSTT enables the evaluation of performance (sport type and motion specific) or the implementation of different methods of training like sprint resisted swimming or sprint assisted training. In the field of rehabilitation, a specific weight training of restricted structures is possible, for example, for patients with arthrosis. Selected applications will be presented. Methods Figure 1 shows a sketch of the PSTT. It consists of a frequency controlled motor system. The power is transmitted with a belt to a rope drum. The special Kevlar® rope with low stretch and a high chemical resistance is guided over two guide pulleys parallel to the water surface. On the end of the rope, the swimmer or the objects can be attached. The motor system allows for two parameters: the force of the rope FR [N] and the rope velocity vR [m/s], the setting. The measuring registration was carried out with a strain gauge (force sensor) and an inductive sensor for velocity. The data were digitized with an analog-digital converter and were graphed with MyoResearch® software. The drag values (passive drag FPD, active drag FAD) were estimated with an average over the plateau of the force course. Results In the field of application oriented research the passive drag in water FPD of swimmer, a geometrical shape and swimming devices like snorkels or swimming rung were estimated. Through simultaneous recordings of the projected frontal surface area (FSA) the calculation of the cW-value was carried out. Based on the supporting application for swimming training results for the "sprint resisted training" (swimming against a defined resistance) and "sprint assisted training" (swimming under pulling support) in field test conditions are represented. Table 1 shows an overview of the selected results. Discussion/Conclusion The "Portable Swim specific Test and Training sdevice (PSTT)" is suitable in the above mentioned field of application. The estimation of passive and active drags are possible. Aming other things this can be used to evaluate the functional abilities of disabled athletes (Kunze & Schega 2003). Furthermore the PSTT allows a swim and motion specific diagnosis of performance during different methods of training. The combination as a device of test and train (simultaneous recording of measuring values) and the portability (tests under laboratory and field conditions) are the eciding advantages in comparison to other similar technical devices.